Enhancing Emotion Regulation and Critical Thinking in Hearing-Impaired Individuals through Sensory Integration Therapy: A Randomized Controlled Trial - Longo , Veronica; Morsali, Sorosh (Psychological Research in Individuals with Exceptional Needs, 2023)
This study aimed to evaluate the effectiveness of Sensory Integration Therapy (SIT) in improving emotion regulation and critical thinking skills in individuals with hearing impairments. A randomized controlled trial was conducted with 30 participants (15 in the intervention group receiving SIT and 15 in the control group). The intervention consisted of ten 75-minute SIT sessions over a two-month period. Emotion regulation and critical thinking were measured at three time points: pre-intervention, post-intervention, and two-month follow-up, using the Difficulties in Emotion Regulation Scale (DERS) and Watson-Glaser Critical Thinking Appraisal (WGCTA), respectively. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests. Significant improvements in emotion regulation were observed in the intervention group from pre-intervention (M = 95.45, SD = 12.78) to post-intervention (M = 81.32, SD = 11.45), and maintained at follow-up (M = 82.67, SD = 12.01). The control group showed no significant changes. For critical thinking, the intervention group’s scores increased significantly from pre-intervention (M = 28.67, SD = 5.23) to post-intervention (M = 36.78, SD = 4.89), and remained high at follow-up (M = 35.54, SD = 4.67). The control group’s scores did not change significantly. ANOVA results indicated significant main effects for time and group for both variables (p < .001), with significant interaction effects (p < .001). Sensory Integration Therapy significantly improves emotion regulation and critical thinking in individuals with hearing impairments, with effects sustained over a two-month follow-up. These findings support the use of SIT as an effective intervention for enhancing cognitive and emotional skills in this population.